2009
DOI: 10.1111/j.1365-2184.2009.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐millimolar concentration of the novel phenol‐based compound, 2‐hydroxy benzoate zinc, induces apoptosis in human HT‐1080 fibrosarcoma cells

Abstract: These results demonstrate that the novel phenolic compound 2HBZ is a potent apoptosis-inducing agent in HT-1080 cells and warrants further investigation as a potential chemotherapeutic agent in primary cancer cell models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…Other studies have shown that 2-HBA [2] or its metal ion complexes, including Na [8], Li [9], Ca [10] or Zn [11 and 12] (Fig. 4), can modulate these cellular processes and subsequently inhibit growth mostly at concentrations in the millimolar range (8)(9).…”
Section: Cell Proliferation Vs Apoptosis and Simple Phenolic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown that 2-HBA [2] or its metal ion complexes, including Na [8], Li [9], Ca [10] or Zn [11 and 12] (Fig. 4), can modulate these cellular processes and subsequently inhibit growth mostly at concentrations in the millimolar range (8)(9).…”
Section: Cell Proliferation Vs Apoptosis and Simple Phenolic Compoundsmentioning
confidence: 99%
“…Willow bark extract, mainly contains p-D-salicin [1], and other SP complexes have been shown to down regulate cell proliferation, inhibit cell cycle, and subsequently induce apoptosis in different cell lines (8)(9)19). Other studies have shown that 2-HBA [2] or its metal ion complexes, including Na [8], Li [9], Ca [10] or Zn [11 and 12] (Fig. 4), can modulate these cellular processes and subsequently inhibit growth mostly at concentrations in the millimolar range (8)(9).…”
Section: Cell Proliferation Vs Apoptosis and Simple Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal ions including calcium (Ca ) showed improved efficacy to various organic compounds against cancer cells. For example, the incorporation of Zn 2+ or Ca 2+ ions improved the apoptotic potentials of HBA compounds [4,10,16] . In addition, platinum-based anticancer drugs have proven to exert highly effective therapeutic potentials in various cancer types [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Although ASA and 2-HBA exert some side effects, their derivatives exhibit less acidity and possess more apoptotic potential. For example, earlier work has highlighted the potential for 4-HBZn to induce apoptosis, particularly in primary CLL and other cancer cells [4,16] . HBCa compounds have also shown their apoptotic potential in human fibrosarcoma HT-1080 cells [10] .…”
Section: Discussionmentioning
confidence: 99%